Ruderal margins of Calamagrostis epigejos and Rubus caesius (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: What is the syntaxonomic affiliation of ruderal tall herbaceous border communities formed by Calamagrostis epigejos and Rubus caesius and their ecological features in Ukraine. Location: Ukraine Methods: analysis of literature data, field research Nomenclature: POWO 2024 Results: The article is focused on the study of ruderal communities formed by Calamagrostis epigejos and Rubus caesius, confined to the areas with relatively poor light soils that form borders between forest, grasslands and communication ways. The herb cover of the studied communities is quite variegated, formed by ruderal, grassland and forest species. Two associations Rubo caesii-Calamagrostietum epigeji and Elymo repentis-Rubetum caesii were identified. They belong to the Convolvulo arvensis-Agropyrion repentis alliance, class Artemisietea vulgaris. The communities of Rubo caesii-Calamagrostietum epigeji association are formed by Calamagrostis epigejos, Convolvulus arvensis, Elymus repens, Silene latifolia, Achillea millefolium, Poa angustifolia. The association Elymo repentis-Rubetum caesii is dominated by shrubs Rubus caesius, R. polonicus, and herbaceous plants Galium aparine, Urtica dioica, Elymus repens, Lamium album, Artemisia vulgaris, Humulus lupulus. Comparative analysis of the species composition of both associations showed that the studied communities form separate blocks of diagnostic species, have some ecological differences from the Convolvulo arvensis-Agropyrion repentis alliance, and at the same time form a dense complex of species of the Artemisietea vulgaris class. According to the synphytoindicative analysis, the communities of the studied associations occupy mesophytic areas on slightly acidic soils enriched with salts, relatively poor in nitrogen, with a low content of carbonates in the soil. The main environmental factors for the formation of association have been established: ombroregime, humidity, soil aeration, nitrogen content in the soil, light and variation of damping. The associations Rubo caesii-Calamagrostietum epigeji and Elymo repentis-Rubetum caesii have a wider range of values of environmental factors than the communities of the Convolvulo arvensis-Agropyrion repentis. This ecotone position of the syntaxons contributes to the formation of a variegated herb cover due to a significant number of random species (ruderal, grassland and forest edges) and is reflected in the range of values of ecological indicators.
Keywords: Artemisietea vulgaris, biodiversity, margin communities, synphytoindication, syntaxonomy, Ukraine